1986
DOI: 10.1002/1097-0142(19861201)58:11<2422::aid-cncr2820581112>3.0.co;2-2
|View full text |Cite
|
Sign up to set email alerts
|

Sclerosing hemangioma of the lung. Immunohistochemical demonstration of mesenchymal origin using antibodies to tissue-specific intermediate filaments

Abstract: A case of pulmonary sclerosing hemangioma of the lung was studied by light microscopy and indirect immunofluorescence using tissue-specific antibodies against intermediate filament subunits. All the tumor cells stained positively and exclusively with antivimentin antibodies thus indicating their mesenchymal origin. In addition, positive staining with cytokeratin antibodies was observed in cells lining cystic spaces and elongated slit-like spaces were occasionally encountered throughout the tumor, disclosing re… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
12
0

Year Published

1988
1988
2020
2020

Publication Types

Select...
6
4

Relationship

0
10

Authors

Journals

citations
Cited by 43 publications
(12 citation statements)
references
References 25 publications
0
12
0
Order By: Relevance
“…However, the histogenesis of PSH has not yet been elucidated since it first description. Subsequent studies have postulated that PSH might originate from mesothelium [5], mesenchyma [6], epithelium [7], and neuroendocrine cells [8]. Recent immunohistochemical studies revealed that PSH might derive from primitive undifferentiated respiratory epithelium [9,10], and molecular study has also demonstrated the same monoclonal pattern in both the round and surface cells, consistent with a ture neoplasm rather than a hamartoma [11].…”
Section: Case Presentationmentioning
confidence: 99%
“…However, the histogenesis of PSH has not yet been elucidated since it first description. Subsequent studies have postulated that PSH might originate from mesothelium [5], mesenchyma [6], epithelium [7], and neuroendocrine cells [8]. Recent immunohistochemical studies revealed that PSH might derive from primitive undifferentiated respiratory epithelium [9,10], and molecular study has also demonstrated the same monoclonal pattern in both the round and surface cells, consistent with a ture neoplasm rather than a hamartoma [11].…”
Section: Case Presentationmentioning
confidence: 99%
“…The lining epithelial cells are termed as surface or cuboidal cells, while the other as round, stromal, or lesional cells. Although SH originally termed a variant of hemangioma (1), subsequent authors have suggested the origin of SH as mesenchymal (2), mesothelial (3) and neuroendocrine (4) derivation. Now there is a consensus that they are epithelial tumors (5, 6).…”
Section: Introductionmentioning
confidence: 99%
“…Pulmonary sclerosing hemangioma (PSH) is an uncommon benign tumor of the lungs, first reported by Liebow and Hubbell in 1956 (1). Its origin has been suggested to be vascular, mesothelial, mesenchymal, epithelial and neuroendocrine (1)(2)(3)(4)(5), but immunohistochemical examination suggests that PSH is derived from primitive respiratory epithelium. It primarily affects Asian women and the female: Male ratio is 5:1 (6,7).…”
Section: Introductionmentioning
confidence: 99%